A comprehensive review of invasion and ecological impacts of introduced common carp (Cyprinus carpio) in Lake Naivasha, Kenya. Issue 4 (16th November 2021) - Mutethya, Eunice; Yongo, Edwine
Abstract: Invasive fish species pose considerable threats to aquatic biodiversity. The fishery of Lake Naivasha was enhanced by introduction of invasive fish species, including carp. The present study examined factors driving successful carp invasions, and their ecological impacts, knowledge of both being essential for management purposes. The present study revealed that carp invaded the lake, probably due to its adaptive traits such as environmental tolerance, fast growth, high fecundity, early sexual maturation and food flexibility. It reduced the biomass of Oreochromis leucostictus, Coptodon zillii and Micropterus salmoides which initially contributed to the fishery through competition and habitat degradation. It is noteworthy that the biomass of Oreochromis niloticus in the lake has recently increased and surpassed carp, attributable to a reduction in its predator ( M . salmoides ) and its biological traits. In terms of ecological effects, carp enhance water turbidity and stimulate algal growth by resuspending sediments and associated nutrients through its foraging activities. Although direct removal has been a useful practice for controlling carp in other places, this approach might be impractical for Lake Naivasha, since carp is the main species sustaining the lake fishery. Instead, implementation of effective management measures, including control of fishing effort, pollution control and protection of surrounding wetlands, would promote recovery and long‐term sustainability of the fishery resources of this lake.